ANALYSIS OF CURRICULUM CHANGE MANAGEMENT AT MADRASAH IBTIDAIYAH - Muhammad Fazis; Ferdino Wedi Sanjaya; Ulya Amelia; yasril yasril; Husnani Husnani (JURNAL EDUSCIENCE, 2026)
Purpose – The transition from the 2013 Curriculum to the Independent Curriculum requires management preparedness at the Lima Puluh Kota State Islamic Elementary School in West Sumatra. However, its implementation still faces obstacles, particularly resistance from senior teachers and limited resources. This study aims to analyze curriculum change management strategies, identify supporting and inhibiting factors, describe the responses of teachers, students, and stakeholders, and formulate recommendations for an effective management model.Methodology – The method used is qualitative with a case study approach. The data collection techniques in this study are interviews, observation, and documentation. The primary data in this study included the principal, teachers, the committee, and students. Meanwhile, secondary data was obtained from relevant literature discussing change management, curriculum, and madrasah ibtidaiyah.Findings – The object of this study was the curriculum change from the 2013 Curriculum to the Merdeka Curriculum implemented at Madrasah Ibtidaiyah Negeri Lima Puluh Kota, West Sumatra. The data analysis technique in this study was triangulation, based on the Miles and Huberman model, which includes four main stages: data reduction, data presentation, conclusion drawing, and verification. The data showed that the success of the change was more determined by the collaboration and leadership of the madrasah principal than by administrative aspects.Contribution – The study concluded that curriculum change management requires a participatory, humanistic approach, supported by organizational culture, the involvement of young teachers, and the active roles of parents and the madrasah committee.